Cameroon : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Performance Criterion, and Financing Assurances Review; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cameroon. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The staff report examines Cameroon's Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. The authorities stressed their interest in a successor IMF program to support Cameroon's medium-term economic objectives. Sound oil revenue management helped contain money growth, and inflation remained generally low. The government significantly lowered its indebtedness to the banking system, which helped to contain money growth despite a large increase in international reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet